Composition evolution of gamma prime nanoparticles in the Ti-doped CoFeCrNi high entropy alloy. (15th April 2018) - Han, Bin; Wei, Jie; Tong, Yang; Chen, Da; Zhao, Yilu; Wang, Jing; He, Feng; Yang, Tao; Zhao, Can; Shimizu, Yasuo; Inoue, Koji; Nagai, Yasuyoshi; et al.
Abstract: The composition evolution of γ′ nanoparticles as a function of aging duration in the Ti-doped CoFeCrNi high entropy alloy was studied by atom probe tomography (APT) and first-principle calculations. The APT results indicate that the evolution behaviors of Co, Fe, and Cr in the Ni3 Ti-type γ′ nanoparticles are significantly different. Co saturates to a stable concentration in the γ′ nanoparticles rapidly in the initial stage of the precipitation, whereas Fe and Cr atoms are incorporated into the γ′ nanoparticles during the coarsening. The APT results are supported by the first-principle calculations from the perspective of the electronic state. Graphical abstract: Unlabelled Image